Understanding Collaboration: generating the multiplication effect. (Introduction) - Wilding, Richard D. (Cranfield University, 2006)
Professor Joachim Milberg, Chairman of the BMW board, said somewhat mystically: "Those who work alone can only accumulate, but those who collaborate intelligently can multiply.” This comment was in relation to the development of the X3 sports utility vehicle developed with the support of Magna Steyr/SFT. Creating a result greater than the sum of the individual parts, the “multiplication effect”, has long been recognised in business. So instead of 1+1=2 a multiplication takes place resulting in 1+1 = 11 or greater! The creation of these win-win relationships is the driver for collaboration in business